Sustainable Development For The Center Of Small Cities - Matra Anugraha; Arif Kusumawanto; Medy Krisnany (Journal of Architectural Research and Design Studies)
As time goes by, cities have developed and grown to be crowded and densely populated area that lead to increasing energy consumption in cities. Thus, some guidelines need to be arranged to control the development of cities. Some of the guidelines are related to floor area ratio (FAR), operational energy, embodied energy, and mobility. Those aspects have strong influence on the consumption of energy in the cities in relation to the sustainability of the area future development. This is in line with the essence and objectives of sustainable cities. To calculate the guidelines, this research used experimental method by the means of computer simulation. The study utilized Rhinoceros with the plug in of Urban Modelling Interface (UMI), in which UMI is software that can simulate and calculate the four aspects correctly and accurately. The guidelines for city development are expected to provide comfortability of living to the community of cities during the development process.